The Role of Medialabs in Regional Cultural and Innovative Policy - Andrzej Klimczuk (Management Trends in Theory and Practice, 2013)
Purpose of this article is to introduce the concept of a new cultural institution, "medialab". Media laboratory is an interdisciplinary institution that combines the tasks of scientific, educational, cultural and artistic institutions. They are spaces in which technology and digital media are designed. Article introduces the main features of medialabs and possible public tasks in the field of regional cultural policy and innovation policy. It also draws attention to the challenges and barriers in the organization and management of these centers.
Keywords: O31; O32; Z11; Z13; 330; creative industries; cultural policy; innovation policy; interdisciplinary institutions; technology transfer; Cultural Industries; Research; Technology